TMM-based study on sound insulation characteristics of laminated cylindrical shell lined with porous materials - Li, Bin; Wang, Ning; Yan, Wenjie; Tian, Ying; Zheng, Zengquan; Kuang, Wenjian (Springer Nature, 2024)
This study utilises the transfer matrix method (TMM) to address the acoustic characteristics of multilayered cylindrical shells lined with porous materials. The TMM theoretical model for the sound transmission loss of composite cylindrical shells with internal porous materials is derived by establishing transfer matrices for the air/composite material interface, composite material/foam interface, foam/air interface and boundary interfaces. The accuracy of the TMM model is validated through a comparison and analysis with experimental results. Building upon this, the impact of porous foam material parameters and types on the structural sound transmission loss is discussed. The results indicate that the use of TMM accurately reflects the acoustic performance of composite structures. Additionally, this model allows for the determination of the influence patterns of porous foam material parameters and types on the acoustic performance of composite structures. In the frequency range of 100–10,000 Hz, the sound transmission loss of the melamine foam-lined composite structure increases with the increase in flow resistance and porosity and the decrease of the tortuosity factor. The use of the porous lining material significantly enhances the structural sound insulation performance.
Keywords: Composite cylindrical shell; Porous materials; Transfer matrix method; Sound insulation characteristics; fi=Energiatekniikka|en=Energy Technology|